Mass Digitization at the Complutense University Library: Access to and Preservation of its Cultural Heritage - Magán, José A.; Palafox, Manuela; Tardón, Eugenio; Sanz, Amelia (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
In the mid-1990s, the Library of the Complutense of Madrid (UCM) applied the growing body of new technologies to a pioneering project: the digitization of a valuable collection of biomedical books. The result of the project was the Dioscorides Digital Library. Up to 2006, however, the pace of digitization was very slow, resulting in only 3,000 books and 50,000 digitized engravings. In September 2006, the Complutense University and Google signed a partnership agreement for the purpose of carrying out large-scale digitization of our public domain collections. The Complutense University Library is participating in this mass-digitization project with the following goals: To improve the discovery of the cultural heritage of Complutense and increase the number of potential readers; To fulfil its public service mission; To preserve and protect the original books; To enhance students’ and faculty research. By early 2011, the Complutense Library had digitized roughly 120,000 out-of- copyright books from the 16th to the 19th centuries. All these materials are easily accessible via the Complutense Library Catalogue, Google Books and HathiTrust Digital Library. The Complutense University of Madrid joined the HathiTrust Digital Library in November 2010, which allowed books digitized by Google to be stored on HathiTrust servers. The HathiTrust Digital Library is both a digital preservation repository and a platform for access. It provides long-term preservation and access services for public domain and in-copyright content from a variety of sources, including Google, the Internet Archive, Microsoft, and in-house partner institution initiatives. In early 2011, the number of HathiTrust public domain volumes reached the two million mark and the collection exceeded eight million volumes. In addition, and complementing the above, the digital content of the Complutense University Library will be aggregated to Europeana during 2011 and 2012.